ANALISIS LIKUIDITAS METODE TRADISIONAL DAN METODE ARUS KAS PT. GAPURA ANGKASA PERIODE 2019-2021 - Desiana Rachmawati; Claveriska Assa Elshania Mae (Sekolah Tinggi Teknologi Kedirgantaraan, 2024)
This study determine the liquidity conditions calculated using the cash flow method and the traditional method, as well as to analyze the financial performance of PT Gapura Angkasa during the covid-19 pandemic and after the covid-19 pandemic. A descriptive quantitative approach was used in this study, and the data used secondary data in the form of financial statements of PT Gapura Angkasa for the period 2019, 2020, 2021 and 2022. Data analysis was carried out by calculating traditional method liquidity ratios (CR and WCTA) and cash flow method (AKO and TH). The results showed that the liquidity condition of PT Gapura Angkasa using the traditional method was decreased in 2020 and more in 2021. Financial conditions that experienced a decline occurred during the Covid-19 pandemic. However, in 2022 after the Covid-19 pandemic, liquidity conditions experienced an increase in ratio. Meanwhile, liquidity conditions using the cash flow method in 2020 occurred a relatively large depreciation, namely during the first year of the Covid-19 pandemic. Liquidity conditions found progress in the second year of the Covid-19 pandemic because they had found financial recovery. While the post-Covid-19 pandemic period in 2022, financial condition showed a superior recovery compared to the previous year.